Validation of Career Planning Guidebook for College Students - Kinayung, Dian; Ardiyanti, Difa; Hidayat, Muhammad (Faculty of Psychology, Universitas Gadjah Mada, 2020)
Career exploration is one of the career development tasks that individuals commonly go through. In reality, these activities may cause problems for specific individuals, including students. Career guidance can assist individuals in successfully passing through this stage of a person’s life. Of the many career intervention models available, no previous research has utilized career planning guidebooks as a form of intervention to help students make career plans. This study aimed to validate a career planning guidebook created by the researcher and test its content and functional validity. Tests of content validity were conducted through professional judgment, while tests of functional validity were conducted via a quasi-experiment. The results showed that all the contents of the career planning guidebook were aligned with the goals of the career planning guidebook (Average of V= 0.6). The experiment results indicated significant difference in perceptions of career planning before and after the intervention (Z=-3.987; p=0.000). The findings concluded that the career planning guidebook is valid, both in terms of content and function.